Chromaticity-tunable phosphor-in-glass for long-lifetime high-power warm w-LEDs1. Issue 31 (21st August 2015) - Chen, Hui; Lin, Hang; Xu, Ju; Wang, Bo; Lin, Zebin; Zhou, Jiangcong; Wang, Yuansheng
<x xml:space="preserve">Abstract</x> This work highlights the practical applications of the PiG luminescent material in long-lifetime high-power warm w-LEDs.